THE RESPONSE OF TWO VARITY OF FABA BEAN (AT FLOWERING STAGE) TO DIFFERENT CONCENTRATIONS OF ALPHA CYPERMETHRIN INSECTICIDE - نهلة حموک (Mesopotamia Journal of Agriculture)
The aim of the present study was to investigate the response of two types of form Faba bean Vicia faba L.(local and Italian), at flowering stage, to different concentration of insecticide alpha cypermethrin. Also, to study these effects on chlorophyll quantity and production of the plant. the experiment was designed according to the International Experimentation System (2x4) according to the Randomized complete Block Design (RCBD) with six replicates .The study involved two factors ; First one included two types of Faba bean (locally and Italian) , the second included different concentrations of the pesticide (distilled water, 0.05, 0.1, 0.2, mg/ml). The alpha cypermethrin pesticide lead to significant decreasing (P-value <0.05) in characteristic of chlorophyll A quantityand in crop yieldingplant height,pod number/plant, seeds number/pod, pod weight (g), pod length and the total weight for each 1000 grain. Which was with direct increase of the concentration. The Italian typerecorded a significant decrease in the chlorophyll A, plant height and pod weight comparing with the local type. it was obvious that the Italian type was more sensitive than the local type toward the pesticide and its negative effect is increasing with the increase of the concentration.